Mainstreaming Ecotheology: Designing Responsive Program Policies at the South Sulawesi Province Regional Office of the Ministry of Religious Affairs - Mulvi Affan Husain (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper analyzes why the ecotheological crisis at the South Sulawesi Regional Office of the Ministry of Religious Affairs has not received serious attention, creating a gap between the Minister of Religious Affairs' national priority programs and regional policy implementation in the face of tangible environmental challenges. This study aims to deeply analyze the root causes of this failure and formulate systemic and responsive policy recommendations. Using a qualitative, descriptive-analytical approach, this paper is based on the analysis of policy documents (Strategic Plans, Performance Reports), related regulations, and in-depth interviews with key informants. The findings show that the absence of an integrated ecotheology framework is not a technical oversight but a systemic failure rooted in three main problems: (1) an unresponsive agenda-setting mechanism for new issues; (2) a rigid, formalistic, and top-down planning process; and (3) the dominance of an anthropocentric jurisprudential paradigm within the bureaucratic culture. Analysis using public policy theories such as the Multiple Streams Framework, Bureaucratic Politics Model, and Advocacy Coalition Framework further clarifies that this problem is a combination of bureaucratic pathology, internal power struggles, and an outdated belief system. Therefore, piecemeal solutions will be ineffective. This study recommends a fundamental policy intervention: the issuance of a Ministerial Regulation (PMA) on the Mainstreaming of Ecotheology. This regulation is proposed as a strategic solution to create a binding legal mandate, overhaul the planning process to be more participatory, and ensure that regional religious programs become relevant, contextual, and impactful in responding to the ecological crisis.